Reamed Interlocking Nails for Tibial Shaft Fractures: A Pathway to Faster Recovery - Feroz Shah, Liaqat Khan, Inam Ur Rahim, Sayed Sohail Akhtar, Harris Ali, Arshan Munir, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: This study aims to evaluate the effectiveness of reamed interlocking nails in the management of closed tibial shaft fractures. Study Design: Descriptive/Observational study. Place and Duration: This multicenter study was conducted at DHQ teaching hospital Timergara and Ali Fatima Hospita Lahore during from the period January, 2023 to June 2023. Methods: A total of 96 patients (both male and female) aged between 20 and 70 years were included in this study. Patient demographic details, including age, sex, and body mass index (BMI), were recorded after obtaining written informed consent. All patients with closed tibial shaft fractures were admitted to the emergency ward and underwent reamed interlocking nail fixation. Postoperative assessments focused on union time, complications, and the overall clinical outcome. Patients were followed for 14 months to track their recovery. Data analysis was performed using SPSS version 20.0. Results: The mean age of the patients was 28.65±8.77 years, with an average BMI of 24.16±6.23 kg/m². Among the 96 patients, 56 (58.3%) were male, and 40 (41.7%) were female. The most common cause of fractures was road traffic accidents (RTA), which accounted for 72 (75%) cases, followed by falls from a height in 18 (18.75%) cases, and other causes in 6 (6.25%). The mean union time for simple fractures was 13.14±4.14 weeks, while for segmental fractures, it was 18.13±6.17 weeks. The overall union rate was 77.5%, with delayed union in 16.25% and non-union in 6.25%. The satisfaction rate among patients was 90%. Conclusion: Reamed interlocking nails proved to be an effective and safe method for managing closed tibial shaft fractures. The overall union rate was 93.75%, with minimal complications, indicating the method's reliability in treating these fractures. Keywords: Interlocking nail, Tibial shaft fractures, Union, Closed fractures, Reamed nails